The Synergy Model for Strengthening the Productivity of Indonesian Halal Industry - Ana Toni Roby Candra Yudha; Nasif Sidquee Pauzi; Rafidah binti Mohd Azli (Universitas Negeri Surabaya, 2020)
Halal industry has become a new commodity that is favoured by all countries around the world, including Indonesia. The main challenge of halal industry development is strengthening its position as a producer in the global halal industry market. This study aims to investigate the number of policy proposals relating to strengthening the productivity of the halal industry in Indonesia and then develop a model of synergy over this matter. This study uses a qualitative study approach, with literature review, observation and interview as data collection methods. The results obtained from this study include several things, specifically; the focus of economic development in Indonesia is fundamentally still focused on the processed industry, which incidentally is dominated by imported raw materials. Based on the results of the analysis of the discussion, the implications of these studies is providing input for authorities such as BPJH, MUI and related ministries to adjust the regulation that address the main business challenge of halal industry. Besides, the government should give special authority to state-owned and private sharia banks to finance the halal industries and agricultural to support their sustainable development.